Effects of processing parameters on cellular ceramics obtained by paraffin emulsified suspensions - Sanches, M. F.
Cellular ceramics were processed by emulsification of alumina suspensions with melted paraffin. Stabilization upon drying was promoted by collagen additions and solidification of the paraffin droplets. Consolidation allows easy elimination of the paraffin droplets on heating at relatively low rate (1-5 degrees C min(-1)), with a plateau at 200 degrees C, and then heating up to the firing temperature (1550 degrees C). A Taguchi plan was used to assess the relative impact of solids loading, paraffin to suspension volume ratio, ultrasound stirring time and heating rate on microstructural features of sintered bodies. Increasing solids loading suppresses the cellular size, with negative impact on total porosity, whereas increasing paraffin: suspension volume ratio contributes to enhance porosity with a slight increase in average cellular size. Ultrasound stirring yields a slight decrease in porosity and also average cellular size. The heating schedule in the early stages of paraffin elimination contributes to changes in cellular size distribution, with important effects on compressive strength. (c) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.